Distribution and Eruptive Volume of Aso-4 Pyroclastic Density Current and Tephra Fall Deposits, Japan: A M8 Super-Eruption - Takarada, Shinji; Hoshizumi, Hideo (Frontiers in Earth Science, 2020)
Estimations of the distribution and eruptive volume of large-scale pyroclastic density current (PDCs) and tephra fall deposits are essential for evaluation of the affected area, long-term volcanic hazards assessments, volcanic activity, and geophysical and petrological quantitative analysis at caldera volcanoes. For this study, the original distributions and eruptive volumes of large-scale PDC (up to 166 km runout distance PDC) and tephra fall deposits derived from the 87-89 ka caldera-forming eruption of Aso volcano in Japan were reevaluated. The original distributions and volumes of PDC deposits just after the eruption were estimated using 3,600 data from geological maps, published research papers, and borehole thickness. The original distributions and volumes of tephra falls were estimated from new isopach maps based on thickness and distribution data of submarine, lacustrine, and subaerial tephra fall deposits. The estimated original volume of the Aso-4 PDC deposits is 340–935 km3 (5.6–14.8×1014 kg). The estimated original volume of the Aso-4 tephra fall deposit is 590–920 km3 (6.0–9.3×1014 kg). The total eruptive volume of the Aso-4 eruption was 930–1,860 km3 (1.2–2.4×1015 kg). This estimation result is about 1.5 to 3 times larger than the previous estimation (>600 km3). Thus, the Aso-4 eruption is now defined as an M8.1–8.4 (VEI8) super-eruption.